Huge right breast lump in male: a diagnostic dilemma as gynecomastia or something else? - ., Krishnaprasad; Reddy, Sandeep; P. N., Sreeramulu; C. A., Shashirekha; Abraham, Amal; Mohan, Padmalakshmi; R., Deepthi (International Surgery Journal, 2018)
Any lump in the male breast is considered as cancer until histologically ruled out otherwise. Breast asymmetry can result from unequal hypertrophy or neoplastic growth, leading fatty tumors to be clinically and radiographically difficult to differentiate from hypertrophy.2 Lipoma is one of the most common benign mesenchymal tumors derived from fatty tissue. Incidence ranges from 12 to 16% of all mesenchymal tumors. We present an unusual presentation of the huge right breast lump in male. A 46 years old male, painless giant sagging right breast. Underwent reduction mammoplasty. Excision biopsy revealed mature adipose tissue separated by thin fibro vascular septate with no neuronal component and malignant transformation. Huge lipoma in male are unusual, requires care evaluation for diagnosis. They associated with excellent prognosis, after successfully intervened. All surgeons should aware of this kind of presentation. To the best of our knowledge this is the first reported case of a huge lipoma of breast in a male. When considering for treatment, the challenging part is reconstruction the breast in full filling a normal symmetrical and aesthetic anatomic structure of the breast. various literatures.